PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR MATA PELAJARAN PPKN SISWA KELAS XI SMA NEGERI 1 MUARO JAMBI: PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR MATA PELAJARAN PPKN SISWA KELAS XI SMA NEGERI 1 MUARO JAMBI - destriani, nela; Salam, M.; Sariani, Dona (Civic Education Perspective Journal, 2022)
One of the problems in this research is the low learning motivation of students at SMA Negeri 1 Muaro Jambi. This is thought to be due to the low level of parental education. To examine this problem, the researcher conducted a study by distributing a questionnaire to selected respondents who were representative of the population at other research sites. This study aims to analyze the educational level of parents and the motivation to study the Civics Education subject for grade XI students at SMA Negeri 1 Muiaro Jaimbi. The type of research in this research is ex post facto quantitative research. Where this research was conducted to determine the value of the two variables, between the independent variable and the dependent variable. By looking for the effect of this independent variable with the dependent variable. This type of research is used by researchers to find out the influence of the level of parental education on the learning motivation of class XI students in SMA Negeri 1 Muaro Jambi. This research was conducted at SMA Negeri 1 Muaro Jambi from November 2019 to September 2020. The research data was obtained by distributing questionnaires to respondents (as the main data). After the questionnaire was returned, the data was processed quantitatively using SPSS. The results of the study showed that out of 77 respondents who were selected to fill out a questionnaire, the influence of their parents' education level on the learning motivation of students in class XI of SMA Negeri 1 Muaro Jambi. There are results in the high category of 38.4% of parents' education level and the high category of 37.1% of learning motivation. The conclusion is that after conducting research by distributing research questionnaires to 77 respondents at SMA Neigeri 1 Miuaro Jamibi, students' motivation to learn has high results because of the influence of parental education. Based on the results of the research carried out, it is recommended that it be investigated in other topics of discussion in a wider scope.